PCR-based sensitive detection of the edible fungus Boletus edulis from rDNA ITS sequences - Lian, Bin; Zang, Jin-ping; Hou, Wei-guo; Yuan, Sheng; Smith, Donald L. (Electronic Journal of Biotechnology, 2008)
Identification of commercially important fungi, such as the valuable edible fungus Boletus edulis can be difficult considering visual or metabolic approaches. Based on phylogenetic analysis of the rDNA ITS sequence, a pair of specific primers was designed for differentiating B. edulis from other mushrooms by PCR. PCR was performed with total DNA as a template at an annealing temperature between 56-60ºC. Positive amplicons were obtained from B. edulis with all DNA templates from fruit bodies and cultured mycelium, but not from other fungal species at an annealing temperature of 60ºC. The result indicated that B. edulis could be clearly distinguished from other fungi by PCR, and there were no misidentifications under the reaction conditions used. The primers were also successfully employed to identify various tissues of B. edulis.